Lansoprazole Alone or in Combination With Gefitinib Shows Antitumor Activity Against Non-small Cell Lung Cancer A549 Cells in vitro and in vivo - Zhao, Xiaoxia; Zhang, Ning; Huang, Yingying; Dou, Xiaojing; Peng, Xiaolin; Wang, Wei; Zhang, Zhe; Wang, Ran; Qiu, Yuling; Jin, Meihua; Kong, Dexin (Frontiers in Cell and Developmental Biology, 2021)
Lansoprazole (Lpz) is an FDA-approved proton pump inhibitor (PPI) drug for the therapy of acid-related diseases. Aiming to explore the new application of old drugs, we recently investigated the antitumor effect of Lpz. We demonstrated that the PPI lansoprazole (Lpz) played a tumor suppressive role in nonsmall cell lung cancer (NSCLC) A549 cells. Mechanistically, Lpz induced apoptosis and G0/G1 cell cycle arrest by inhibiting the activation of signal transducer and activator of transcription (Stat) 3 and the phosphoinositide 3 kinase (PI3K)/Akt and Raf/ERK pathways. In addition, Lpz inhibited autophagy by blocking the fusion of autophagosomes with lysosomes. Furthermore, Lpz in combination with gefitinib (Gef) showed a synergistic antitumor effect on A549 cells, with enhanced G0/G1 cell cycle arrest and apoptosis. The combination inhibited Stat3 phosphorylation, PI3K/Akt and Raf/ERK signaling, affecting cell cycle-related proteins such as p-Rb, cyclin D1 and p27, as well as apoptotic proteins such as Bax, Bcl-2, caspase3 and poly (ADP-ribose) polymerase (PARP). In vivo, coadministration with Lpz and Gef significantly attenuated the growth of A549 nude mouse xenograft models. These findings suggest that Lpz might be applied in combination with Gef for NSCLC therapy, but further evidence is required.